2001
DOI: 10.1002/gps.480
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Chinese suicide attempters admitted to a geropsychiatric unit

Abstract: Our study confirms previous Western reports that depressive disorders are commonly manifested in elderly suicide attempters. There were differences in the motives and methods employed for the suicides, possibly due to cultural difference and/or sample source. Most of the suicide attempters exhibited a favourable response with hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
1
26
1
Order By: Relevance
“…In view of the identified challenges, what this review supports firstly is the importance of our social and cultural backgrounds which, as Yang et al (2001) and Chan et al (2007) point out, significantly influence the expression of any of the contributing factors identified, as well as defining the barriers to seeking professional support. Full assessment with attention to sociocultural factors as well as the optimum management of mental dis orders is required, as is the promotion of more appropriate problem solving methods (International Association for Suicide Prevention, 2014).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…In view of the identified challenges, what this review supports firstly is the importance of our social and cultural backgrounds which, as Yang et al (2001) and Chan et al (2007) point out, significantly influence the expression of any of the contributing factors identified, as well as defining the barriers to seeking professional support. Full assessment with attention to sociocultural factors as well as the optimum management of mental dis orders is required, as is the promotion of more appropriate problem solving methods (International Association for Suicide Prevention, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…None of the comparison subjects had bipolar disorder. Similarly, Yang et al (2001) also found that depressive disorders (major depression or dysthymic disorders) were the most common diagnoses for older Taiwanese attempters but organic mental disorders were rarely diagnosed. In the UK study by Dennis et al (2005), approximately 40% of both selfharm and control groups experienced severe life events during the 6-month study period; comparable with earlier UK studies.…”
Section: Depressionmentioning
confidence: 81%
See 3 more Smart Citations